2020
DOI: 10.1038/s41598-020-73180-3
|View full text |Cite|
|
Sign up to set email alerts
|

CT-based dentulous mandibular alveolar ridge measurements as predictors of crown-to-implant ratio for short and extra short dental implants

Abstract: The purpose was to predict the crown-to-implant ratio variation in the edentulous posterior mandibles rehabilitated with short dental implants. Hence, vertical and horizontal dimensions of dentulous posterior mandibles in a sample of 18- to 25-year-olds were measured, and correlations of these dimensions with sex and site were investigated. Mandibular computed tomography scans from 100 subjects were considered. Vertical and horizontal bone and tooth measurements were taken at the sites of the second premolar (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
1
5
0
1
Order By: Relevance
“…DEBM and AAB are xenografts since they are derived from animals. Even though there are only a few randomized controlled clinical trials comparing DEBM and AAB in the literature [35,36], our results are consistent with previous findings. In fact, both materials share similar characteristics in terms of inflammation and new bone formation, as shown in Table 1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…DEBM and AAB are xenografts since they are derived from animals. Even though there are only a few randomized controlled clinical trials comparing DEBM and AAB in the literature [35,36], our results are consistent with previous findings. In fact, both materials share similar characteristics in terms of inflammation and new bone formation, as shown in Table 1.…”
Section: Discussionsupporting
confidence: 92%
“…Caucasian patients aged ≥25 years with at least one atrophic posterior maxilla with a residual crest height ≤ 4 mm who needed maxillary sinus lift for dental implant placement were eligible for the trial [36,37]. The residual crest height was evaluated by Cone Beam Computed Tomography (CBCT).…”
Section: Patient Selectionmentioning
confidence: 99%
“…The previous studies concentrated on mutually dentulous and edentulous cases. The length and height of the residual bone were analyzed in healthy with full teeth cases will help to focus on the regeneration processes of bone, for prediction any necessity of adding bone substitutes, with the choice of most appropriate implant size [29].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of atrophy of the alveolar process was calculated at each marking, which was equal to the difference in height at the given point, measured on the model obtained before prosthetics and the height measured at the indicated period. To verify the results, the degree of atrophy of the alveolar processes was also determined by the second method the authors have chosen at the same time as indicated above ( Sivolella et al, 2020 ). The basis of this method is the measurement of the volume of the polymerized corrective impression mass, which fills the space between the prosthesis and the tissues of the prosthetic area ( Ribeiro et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%